Micro Marsupialization Versus Modified Micro Marsupialization in The Management of Mucocoele of Lower Lip: Micro Versus Modified Marsupialization for Mucocele - Akosh, .; Kumbhar, Aftab Ahmed; Shaikh, Tarique Hussain; Arif, Lubna M; Siddique, Saadia; Lakho, Farzana (Pakistan Journal of Health Sciences, 2024)
The most prevalent kind of soft-tissue cyst of the small salivary glands in the lower lip is called a mucocele. It usually manifests as a fluctuating, bluish, not tendering sub-mucosal swelling with a usual overlying mucosa. The lower lip is where mucoceles are most frequently found, despite the fact that small salivary glands are present in most areas of the oral cavity with the exception of the gingiva, Anterior hardpalate and tip of the tongue. This is most likely because this area experiences more mechanical trauma than other locations. Objective: To compare the outcomes of surgical technique between micro- marsupialization and modified micro marsupialization in treatment of mucocele of lower lip. Methods: Experimental study was conducted at Department of OMFS, LUMHS, Jamshoro, by convenience sampling technique in time frame of Six months. Patients were called into two groups at random. Patients in group A were managed by micro-marsupialization and in group B by modified micro-marsupialization. All the patients were followed till one week to assess wound healing time and pain. The analysis of data was conducted using SPSS version 26.0. Results: In comparison of group A and B, wound healing time was noted as 9.7 ± 3.1 and 10.9 ± 4.01 days (P=0.180), duration of surgery 30.2 ± 3.7 and 29.9 ± 3.6 minutes (P=0.727) and postoperative pain at 7th day was noted 2.7 ± 1.8 and 2.17 ± 1.7 (P=0.257), respectively. Conclusion: It was concluded that insignificant difference was noted between micro-marsupialization and modified micro-marsupialization in outcomes of surgical technique in treatment of mucocele of lower lip.